Determinants of regional growth and convergence in Germany - K. Haaf; Clemens J. M. Kool (Utrecht University, Utrecht University School of Economics, Tjalling C. Koopmans Research Institute, 2017)
In this paper, we analyse the sources of real per capita income growth and convergence in the 16 German states over the period 1995-2014 using a panel approach. The empirical analysis applies the popular growth – initial income equation. We augment the basic model specification with a trend term and a crisis dummy. We then augment the model with additional explanatory variables and account for non-linear interaction effects. Overall, we find evidence of slow but significant convergence once the crisis and a trend are appropriately accounted for. Internal migration has a positive impact on growth in the East and thus contributes to the convergence between Eastern and Western states. Horizontal tax equalisation is ineffective in promoting growth and convergence, but we do find some evidence that federal supplementary grants have contributed to convergence between grant receiving and non-receiving states. Structural funding is found to have opposing growth effects on Eastern and Western states and has significantly promoted convergence.
Keywords: 330; Internal migration; Fiscal equalisation; Structural funding; Panel approach; Interaction effects